A molecular design towards sulfonyl aza-BODIPY based NIR fluorescent and colorimetric probe for selective cysteine detection. Issue 17 (10th March 2021) - Pham, Thanh Chung; Choi, Yeonghwan; Bae, Chaeeon; Tran, Cong So; Kim, Dongwon; Jung, Ok-Sang; Kang, Yong-Cheol; Seo, SungYong; Kim, Hyun Sung; Yun, Hwayoung; Zhou, Xin; Lee, Songyi
Abstract : A new fluorescent and colorimetric probe based-on sulfonyl aza-BODIPY (BDP-1–3 ) are designed and synthesized for selective cysteine detection. Abstract : Cysteine (Cys), homocysteine (Hcy) and glutathione (GSH) are essential biothiols for cellular growth, metabolism, and maintenance of a biological system. Thus, the detection of biothiols is highly important for early diagnosis and evaluation of disease progression. In this article, a series of sulfonyl aza-BODIPYs was synthesized, characterized, and examined by 1 H-NMR, 13 C-NMR, crystallization, photophysical properties and DFT calculation. Among these structures, a fluorescent probe, BDP-1, exhibited selective detection of Cys among various biothiols via nucleophilic aromatic substitution and typical size of Cys molecules. BDP-1 showed color change and near-infrared (NIR) fluorescence enhancement after reaction with Cys to generate BDP-OH, confirmed by HRMS. The red shift of absorption wavelength showed a similar tendency resulting in time-dependent density functional theory (TD-DFT). Furthermore, the calculated detection limit of BDP-1 toward Cys was 5.23 μM. This probe facilitates the colorimetric and fluorescent detection of Cys over other biothiols.